Career Reorientation for Accounting Students in the Era of Artificial Intelligence - Nur Fadilah Arsyad; Khalsja Oktaviani Kadir; Tia Latifa Suma; Savira Ramadhani Mokodongan (CV Edujavare Publishing, 2026)
The rapid development of Artificial Intelligence (AI) is transforming the accounting profession and requires accounting students to develop competencies that meet future workplace demands. This study aims to examine students' perceptions of AI disruption, academic competency readiness, and career interest in the AI era. A qualitative descriptive approach was employed involving eight undergraduate accounting students from Universitas Negeri Gorontalo selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis. The findings reveal that students perceive AI as a tool for automating routine accounting tasks rather than replacing accountants. Although the curriculum provides adequate fundamental knowledge, it has not fully addressed current industry needs, encouraging students to pursue self-directed learning. Career interests remain focused on accounting professions while increasingly emphasizing digital competencies and technology-oriented accounting roles